Rancang Bangun Aplikasi Inventaris Barang Berbasis Android Pada PT. Nuansa Indah Mane - riana Riana; Andi Cristian; Yuntari Purbasari (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
Almost all large companies have switched from manual systems to computer-based systems; computer-based systems are beneficial and facilitate company performance using application assistance. This application will be used to reduce the user number of users. Among them are recording incoming, returning, and outgoing goods. Therefore, the application for a company is beneficial and can improve agency performance. The Inventory Information System used by Nuansa Indah Mane Limited Liability Company still uses a manual system, namely Microsoft Excel, so searching for inventory data is slow. Therefore, this thesis is carried out to make an inventory design that is easy to use so that it can facilitate access to the desired information and can facilitate the management of file data. The researcher of this thesis is an Android-based product inventory design, while the system development method uses the RAD (Rapid application development) method